Multisensitive Swelling of Hydrogels for Sensor and Actuator Design. Issue 7 (15th May 2020) - Ehrenhofer, Adrian; Binder, Simon; Gerlach, Gerald; Wallmersperger, Thomas
Abstract : A main characteristic of hydrogels is their multisensitivity, i.e., the material's capability to respond to multiple stimuli such as temperature, chemical concentration or light. Most modeling approaches to swelling in the literature deal with the monosensitive behavior of hydrogels. Herein, two approaches to the modeling of multisensitive sensors and actuators are proposed: the N ‐field method and the trajectory method. They are derived using experimental data of the bisensitive hydrogel [ net ‐P(AMPS‐ co ‐NiPAAm)]‐ sipn ‐PAMPS. It is sensitive to sodium salt concentration and temperature. For the trajectory method, the procedure for the generalized representation of the material behavior is presented. Applying the Temperature Expansion Model, this is implemented in Abaqus and the results of verification simulations are given. The trajectory method is capable of representing the multisensitive behavior of hydrogels. The method is easy to implement in commercial Finite Element tools based on the free‐swelling data of the material. Simulation results of the free swelling are in excellent agreement with the given calibration data. The obtained swelling behavior can be combined with mechanical loads and arbitrary boundary conditions to form more complex setups. The current work allows a deeper understanding of complex multifunctional materials, such as hydrogels, and their application in sensor or actuator devices. Abstract : A main characteristic of hydrogels is their multisensitivity, i.e., the material's capability to respond to multiple stimuli. This topic is approached from the engineering perspective. Two modeling approaches are derived combined with experimental data of the bisensitive hydrogel [ net ‐P(AMPS‐ co ‐NiPAAm)]‐ sipn ‐PAMPS. The current work allows a deeper understanding of complex multifunctional materials and their application in sensor or actuator devices.